REPRESENTASI EROTISME BARU DALAM KOMIK TAHILALATS TAHUN 2015-2016 - Saputri, Nur Amala (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
This study describes symbols and signs containing erotic elements in the Tahilalats comic by Nurfadli Mursyid. The unit of analysis based on two main components in Tahilalats. The two components are Instagram interactive feature which is used as Tahilalats medium, and comic content aspect. Interactive features include comments, and in terms of comic content including basic comic elements: panels, balloons, captions, & illustrations. Data were analyzed by using qualitative analysis method of semiotics Roland Barthes. The results of the study show symbols of new eroticism that symbolize incest, transgender, and masochism in Tahilalats. Refering to the critical paradigm, there are certain ideologies related to the background of Nurfadli as Buginese through the culture of incest, the figure of bissu, and calabai. On the other hand, the use of Instagram as a comic medium has changed the way of presentation and enjoying erotic content in comics. The presence of features in the platform Instagram also makes the netizens play a major role in constructing erotic content in the Tahilalats. To cite this article (7th APA style): Saputri, N. A. (2018). Representasi Erotisme Baru dalam Komik Tahilalats Tahun 2015-2016 [The Representation of New Eroticism in the Tahilalats Comic 2015-2016]. Journal Communication Spectrum, 8(2), 190-207. http://dx.doi.org/10.36782/jcs.v8i2.1854